Leak Detection in Pipelines Using Wavelet Transform and Cepstrum Analysis Methods - Gigih, Priyandoko; Ghazali, Mohd Fairusham (International Journal of Electrical, Energy and Power System Engineering, 2021)
Nowadays, a piping system is one of the important features in either home or industrial user. Leak in piping systems is a major operational problem around the world. Leaks result to loss in the fluid through the flow and automatically affect to the economy of the user. Objective of this research is utilizing the signal processing using Wavelet Transform and Cepstrum Analysis methods to leak detect in pipeline. After experiment has been completed, the data analysis process by using Matlab Software takes place. The result shows that the accuracy of the leak location detection is accurate with small error results below 10%.